Traffic safety and human behavior - Shinar, David (Elsevier, 2007)
The aim of the book is to present a state of the art assessment of highway safety from a 'user-centered' perspective. The user in this case is the driver, the cyclist, and the pedestrian. The book will cover driving behavior from the motivational and information-processing perspective, and following a consideration of several models that have been proposed to describe driver behavior, different topics will cover the major research issues of the past decade. These include the impact of fatigue, aggression, personality, alcohol and other drugs, on driving behavior and crash involvement; the vari.